A Polymer for Application as a Matrix Phase in a Concept of In Situ Curable Bioresorbable Bioactive Load-Bearing Continuous Fiber Reinforced Composite Fracture Fixation Plates - Plyusnin Artem; He Jingwei; Elschner Cindy; Nakamura Miho; Kulkova Julia; Spickenheuer Axel; Scheffler Christina; Lassila Lippo VJ; Moritz Niko (MDPI, 2025)
The use of bioresorbable fracture fixation plates made of aliphatic polyesters have good potential due to good biocompatibility, reduced risk of stress-shielding, and eliminated need for plate removal. However, polyesters are ductile, and their handling properties are limited. We suggested an alternative, PLAMA (PolyLActide functionalized with diMethAcrylate), for the use as the matrix phase for the novel concept of the in situ curable bioresorbable load-bearing composite plate to reduce the limitations of conventional polyesters. The purpose was to obtain a preliminary understanding of the chemical and physical properties and the biological safety of PLAMA from the prospective of the novel concept. Modifications with different molecular masses (PLAMA-500 and PLAMA-1000) were synthesized. The efficiency of curing was assessed by the degree of convergence (DC). The mechanical properties were obtained by tensile test and thermomechanical analysis. The bioresorbability was investigated by immersion in simulated body fluid. The biocompatibility was studied in cell morphology and viability tests. PLAMA-500 showed better DC and mechanical properties, and slower bioresorbability than PLAMA-1000. Both did not prevent proliferation and normal morphological development of cells. We concluded that PLAMA-500 has potential for the use as the matrix material for bioresorbable load-bearing composite fracture fixation plates.